2022
DOI: 10.1111/1747-0080.12735
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of adequacy of fruit and vegetable intake as a barrier to increasing consumption

Abstract: Aim To investigate New South Wales adults' perceived adequacy of their fruit and vegetable consumption and to identify the barriers to consumption. Method An online cross‐sectional survey of a sample of adults in New South Wales (n = 1603) in February 2019 measured self‐reported fruit and vegetable intakes, perception of consumption adequacy and barriers to consumption. Proportions of participants whose reported consumption met the daily recommended serves of fruit and vegetables per day were calculated. Chi‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…The deficiency in fruit and vegetable intake largely indicates that their busy lifestyles are the primary obstacle, mainly due to the time commitments associated with attending classes [ 21 , 22 ]. Furthermore, the perception of already having sufficient intake serves as a significant barrier, leading to limited efforts to increase fruit and vegetable consumption within this demographic group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency in fruit and vegetable intake largely indicates that their busy lifestyles are the primary obstacle, mainly due to the time commitments associated with attending classes [ 21 , 22 ]. Furthermore, the perception of already having sufficient intake serves as a significant barrier, leading to limited efforts to increase fruit and vegetable consumption within this demographic group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study aimed to build on the two former studies by using the same intervention research design and investigated the impact of the Australian Dietary Guidelines 2&5 education message (2&5 education nudge) placed in supermarket shopping trolleys on shopper F&V purchases. The reason for testing the impact of a 2&5 education nudge message is because the literature suggests that of adults consuming less than the F&V guidelines, more than 1 in 5 perceived that they were eating enough fruit and more than one‐half perceived they were eating enough vegetables (Wellard‐Cole et al., 2023). This is also supported by previous Australian research (Hill et al., 2020) which reported that more than 3 in 4 adults had insufficient or poor F&V knowledge resulting in lower F&V intake compared to those with adequate F&V knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…
Fruit and vegetable intakes are major modifiable determinants of risk for non-communicable disease (1) , yet intake levels remain low (2) and multiple barriers (cost, access, perishability, preparation skills) exist (3,4) . 100% fruit and vegetable juices contain key micronutrients and bioactive compounds (5)(6)(7) and may help circumvent these barriers to consumption (6,7) .
…”
mentioning
confidence: 99%